Uji Antagonisme Trichoderma harzianum Dan Azotobacter chroococcum Terhadap Rhyzoctonia solani, Sclerotium rolfsii dan Fusarium oxysporum secara in-vitro - A. Marthin Kalay; Abraham Talahaturuson; Wilhemina Rumahlewang (Faculty of Agriculture, Pattimura University, 2018)
Damage to plants by pathogenic fungi is often found in nurseries and field. Biological control offers a promising alternative for managing diseases in plants because they are environmentally friendly compared to pesticides. The aim of the study was to test the power of the antagonism of Trichoderma harzianum and Azotobacter chroococcum on solid organic media